Unusual complication after laparoscopic left nephrectomy for renal tumour: a case report - Arantxa Arruabarrena; Juan Santiago Azagra; Jean Francoise Wilmart; Ioan Bachner; Dan Manzoni; Martine Goergen (Videosurgery and Other Miniinvasive Techniques)
In splenic rupture after blunt trauma, iatrogenic spleen injury or non-traumatic cases it is essential that the surgeonmakes correct decisions. Conservative treatment must include continual monitoring and repeated, stringent evaluationof the splenic injury (the American Association for the Surgery of Trauma – AAST) in order to avoid any delay indiagnosis of delayed spleen rupture and the high mortality it causes. We present the case of an unexpected complicationafter radical nephrectomy performed for renal cell carcinoma. A 61-year old man sought medical help for acuteabdominal pain. He presented with some cardiovascular risk factors (diabetes mellitus, smoker of 30 cigarettes perday) and moderate alcohol use. In the Emergency Unit, computed tomography scan revealed an incidental tumour ofthe left kidney. Nephrectomy via the laparoscopic approach was done without any iatrogenic complications, with lessthan 500 cc of blood loss. Firm adhesions between the spleen and abdominal wall, which caused some minor tractionthat resulted in a small subcapsular haematoma, were the only surprising intraoperative finding. Within the first 6 h,the patient presented with haemodynamic instability, while the drain evacuated less than 50 cc of discharge.However, CT scan showed that subcapsular haematoma had increased to the size of 10 × 10 cm without freeperitoneal fluid present. Unfortunately, 6 h later emergency surgery had to be performed due to rupture of thesubcapsular splenic haematoma. Massive haemoperitoneum was evacuated and the splenic capsule was the onlyremnant of the spleen that could be found on re-intervention. So far, it is the first case describing an increasing subcapsularhaematoma of the spleen, most likely caused by the traction of firm adhesions to the organ. We discussmeans to avoid such a complication: with liberation of the adhesions, placement of a perisplenic mesh, embolizationof the splenic artery or subcapsular nephrectomy. An acute splenic rupture or delayed one demands from the surgeonpractical knowledge of how to prevent subcapsular haematoma and how to treat splenic rupture.